Improving Quality of Light Commercial Vehicle Using PDCA Approach - Nabiilah, Ab Rahim; Zamzuri, Hamedon; Faiz, Mohd Turan (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
Good quality coating in painting process of light commercial vehicle is important to reduce cost and concurrently achieve customer satisfaction. The PDCA-cycle approach is utilized to reduce the defects in the electrodeposition process. In this study the bits defect on the electrodeposited body is investigated. A systematic quality improvement plan and optimization are performed. The application of the PDCA-cycle improved 65% of bits and reduced 34% of sanding man hour.